ANALISIS PENGARUH KUALITAS LAYANAN, MARKETING MIX, DAN PROMOTIAL MIX TERHADAP KEPUASAN YANG BERDAMPAK KEPADA LOYALITAS PELANGGAN - Rakhmat Muqoddim; Ahmad Yani; Zufriady Zufriady (JEM Jurnal Ekonomi dan Manajemen, 2018)
This research uses three variables, service quality (X1), Marketing Mix (X2) and Promotion Mix (X3) as an exogenous variable to Satisfaction (Y) as intervening variable and Customer Loyalty Syifa Printing Pangkalpinang (Z) as an endogenous variable. The purpose of this study is to examine the effect of the influence of service quality, marketing Mix, Promotion Mix, Against Satisfaction Affecting Customer Loyalty On Printing Syifa Printing Pangkalpinang. The research method used is surveyed respondent method and the object of research is Printing of Syifa Printing Pangkalpinang. This research uses the method of analysis in the form of quantitative analysis of primary data direct research results from the field. As a tool in statistical data processing used SPSS program version 22. The results of the study found that the Quality of Service (X1), Marketing Mix (X2) and Promotion Mix (X3) together affect the Customer Satisfaction at Printing Syifa Printing Pangkalpinang. And Customer Satisfaction partially influence on customer loyalty at Printing Syifa Printing Pangkalpinang